THE EFFECT OF CURRENT RATIO, RETURN ON ASSETS, COMPANY SIZE, AND BUSINESS RISK ON CAPITAL STRUCTURE WITH SALES STABILITY AS A MODERATING VARIABLE IN COMPANIES IN THE PRIMARY CONSUMER GOODS SECTOR FOR THE 2017-2021 PERIOD - Yani, Fitri; Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Wijaya, Ricky; Davin, Michael Elian (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
Penelitian ini bertujuan untuk menguji pengaruh current ratio, return on assets, ukuran perusahaan, dan risiko bisnis terhadap struktur modal dengan stabilitas penjualan sebagai variabel moderasi pada perusahaan sektor barang konsumsi primer periode 2017-2021. Keunggulan penelitian ini pada penggunaan stabilitas penjualan sebagai variabel moderasi. Sampel penelitian sebanyak 33 perusahaan. Metode analisis data dalam penelitian ini menggunakan Analisis Regresi Linear Berganda dan Moderated Regression Analysis dengan bantuan software Smart PLS. Hasil penelitian membuktikan bahwa current ratio berpengaruh negatif terhadap Struktur Modal. Return on assets, Ukuran Perusahaan, dan Risiko Bisnis berpengaruh negatif tetapi tidak signifikan terhadap Struktur Modal. Semua pengujian moderasi menunjukkan hasil yang tidak signifikan. Disarankan perusahaan memperhatikan current ratio sebagai variabel yang berpengaruh negatif terhadap struktur modal. This study aims to examine the effect of the current ratio, return on assets, company size, and business risk on capital structure with sales stability as a moderating variable in companies in the primary consumer goods sector for the 2017-2021 period. The advantage of this research is the use of sales stability as a moderating variable. The research sample is 33 companies. The method of data analysis in this study uses Multiple Linear Regression Analysis and Moderated Regression Analysis with the help of Smart PLS software. The results of the study prove that the current ratio has a negative effect on Capital Structure. Return on assets, company size, and business risk have a negative but not significant effect on capital structure. All moderation tests show insignificant results. It is recommended that companies pay attention to the current ratio as a variable that has a negative effect on capital structure.